(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
Since the birth of Pakistan in 1947, there had been a consistent assault on the language, heritage and culture of East Bengal by the Pakistani government. The authoritarian and aggressive behaviour of the central administration of Pakistan and its adherents in the cultural sphere had pushed the Bengali community into a crisis of existence. In response, intellectuals, artists and cultural activists of East Pakistan became involved in the struggle to preserve Bengali cultural heritage and freedom. As part of this cultural resistance, literary and cultural conferences were organised in various cities of East Pakistan from 1948 to 1957. Women’s participation was evident in these literary-cultural conferences. Despite their courageous participation in cultural activities that surpassed contemporary social conservatism, their role remained largely unexplored. Therefore, there is a need to evaluate women’s role separately in the cultural movement of that period. The aim of this article is to explore and analyse the diverse and multifaceted contributions of women in the literary and cultural conferences of East Pakistan. This paper presents an analysis of women’s participation and performance in the literary and cultural conferences of East Pakistan. The research utilizes both primary and secondary sources that include autobiographies, newspapers, interviews of cultural movement organisers and artists, books and scholarly articles. Following a historical research method, the paper concludes with the findings that nonconformist activism, spontaneity, unprecedented courage of Bengali-women were significant contributors in the cultural resistance movement against the oppressive government of Pakistan. JASBH, Vol. 69(2), 2024, pp. 239-258